Clinical Supervision of Madrasah's Head in MTs Darul Huda Bandar Lampung - Dermawan, Oki; Gumilang, Gumilang (Universitas Islam Negeri Raden Intan Lampung, 2020)
The implementation of clinical supervision of madrasah principals aims to shape the performance of educators becoming more professional in carrying out their functions as supervisors. The madrasa head must be able to master his duties and carry out his duties properly, he is responsible for all madrasa activities regulating the teaching and learning process, regulating matters relating to student affairs, business, finance and regulating relations with the community. In a management it is explained that one of the most important aspects in an organization is the way a person leads to the organization being led, a good organization will produce excellent results starting from the structure, human resources, and others. While the nature of leadership is the activity of leading the process of influencing subordinates or others. Formulation of the problem: Based on the background of the problem above, then the problem is